Comparison of Vickers microhardness of undoped and Ru doped BSCCO glass ceramic materials - Öztürk, Özgür; Aşıkuzun, Elif; Taşçı, Ahmet Tolga; Gökçen, Tuğba; Ada, Hakan; Koralay, Haluk; Çavdar, Şükrü (Springer Science and Business Media LLC, 2017)
In this study, effect of substitution ratio on the mechanical and structural properties of Bi1−xRuxPb0.2Sr2CaCu2O10+δ system, that is prepared in the ratios of x = 0.0, 0.025, 0.050, 0.075, is investigated. Samples are prepared with glass ceramic method and sintered at 845 °C. XRD and SEM measurements are performed for structural analyses, and Vickers micro-hardness measurements are carried out at different applied load (0.245 ≤ F ≤ 2.940 N) in order to investigate the mechanical performance of the Ru doped Bi1−xRuxPb0.2Sr2CaCu2O10+δ system. Experimental results of Vickers micro-hardness analyses are performed using the Meyer’s law, the proportional samples resistance model, the elastic/plastic deformation model, the Hays–Kendall approach and the indentation induced cracking (IIC) model. All analyses results are exhibited reverse indentation size effect behavior. The measured hardness values increase with increasing the applied load. Finally, IIC model is determined as the most successful model describing the mechanical properties of our samples.
Keywords: BSCCO; 2. Zero hunger